Training needs analysis (TNA): the foundation for designing a tailored training program - Costa, Gilson Cezar Alves da; Soares, Marison Luiz (Brazilian Journal of Production Engineering, 2026)
To address constant changes and challenges, the world of work requires continuous human learning and lifelong education. With the aim of identifying priority learning needs and promoting the rational use of organizational resources, researchers have investigated Training Needs Analysis (TNA) methodologies empirically applicable to the workplace context. This article adopts a bibliometric approach to map the scientific production on TNA and subsequently articulates the main findings of the literature with the practices observed in the Brazilian Federal Public Administration (APF). Nine theoretical-methodological propositions were selected for discussion. The results indicate that the use of multiple TNA methods in the APF contributes to balancing the strengths and limitations of each approach, expanding the potential effectiveness of development actions.